Sifarish: Understanding the Ethical Versus Unethical Use of Network-Based Hiring in Pakistan - Nadeem, Sadia (Journal of business ethics, 2019)
The role of affective ties and informal social networks in management practices is recognised across many parts of the world; guanxi in China, yongo in Korea, blat in Russia and wasta in the Arab World are some manifestations. This paper explores the role of such informal networks in Pakistan by studying the role of sifarish—the act of achieving ends on the basis of network connections—in hiring in Pakistan using thematic analysis of inductively collected qualitative data from 104 individuals from four large organisations. Using social network and social capital theory, the paper highlights the key characteristics of affective networks in Pakistan, comparing them to social networks in other cultural settings. Further, the concept of ethical relativism is used to create a distinction between ethical and unethical sifarish. Thus, the paper enhances understanding of HRM in Pakistan, and contributes towards the literature on cross-cultural HRM, social networks and ethical relativism.